A glimpse into the future of genome-enabled plant biology from the shores of Cold Spring Harbor. Issue 1 (December 2016) - Rhee, Seung; Parker, Jane; Mockler, Todd
Abstract A report on the 10th plant genome meeting entitled 'Plant genomes and biotechnology: from genes to networks', held at Cold Spring Harbor Laboratory, 2–5 December, 2015.